Peran Kelompok Informasi Masyarakat (KIM) dalam Diseminasi Informasi Melalui Media Sosial di Kelurahan Gundih Kota Surabaya - Wardhana, Shofi Hadi (Universitas Islam Negeri Sunan Ampel, 2022)
The public's thirst for information is growing at a tremendous rate right now. One of the government's work projects to assist in the creation of an information society is the Community Information Group (KIM). The purpose of this program is to optimize the usefulness of information in daily life. The pattern of KIM diffusion, KIM's function in the dissemination process, and the locals' reaction to KIM in Gundih Village are the issues examined in this study. The present study employs a qualitative research design utilizing descriptive data gathering procedures, including observation, interviews, and documentation. Tallcot Parson's functional structural theory is the theory that makes sense of the things that take place in the Role of KIM in Information Dissemination review. Based on this survey, it can be said that WhatsApp, Instagram, blogs, YouTube channels, and blogs are the main social media platforms used for KIM propagation. Social media use is maximized to bridge the knowledge gap. The community and local Stakeholders benefit from KIM's role as a facilitator, mediator, and innovator in Gundih Village, despite the challenges posed by social media use. Residents of Gundih and local Stakeholders (RT/RW) responded well to KIM Gundih. The fact that the people of Gundih are ignorant of the responsibilities and operations of KIM in their community further contributes to the negative responses